If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9c + -11 = c + 25 Reorder the terms: -11 + 9c = c + 25 Reorder the terms: -11 + 9c = 25 + c Solving -11 + 9c = 25 + c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. -11 + 9c + -1c = 25 + c + -1c Combine like terms: 9c + -1c = 8c -11 + 8c = 25 + c + -1c Combine like terms: c + -1c = 0 -11 + 8c = 25 + 0 -11 + 8c = 25 Add '11' to each side of the equation. -11 + 11 + 8c = 25 + 11 Combine like terms: -11 + 11 = 0 0 + 8c = 25 + 11 8c = 25 + 11 Combine like terms: 25 + 11 = 36 8c = 36 Divide each side by '8'. c = 4.5 Simplifying c = 4.5
| 5x+155=11x-13 | | 0.4x-1.8=-3.7 | | 6x-19x=0 | | 3x-7x+12=32 | | (-4+8x)=6 | | =4x^2-19xy-5y^2 | | y=-(2/3)40+30 | | y=-(2/3)20+30 | | -3(4b-10)=.50(-24b+60) | | y=-(2/3)15+30 | | 3x+4(x-5)=1 | | -2=x^2-4x-5 | | y=-1*-1+-1 | | 2n+7=2n+12 | | -0.8r-3.1=-8.3 | | y=-(2/3)10+30 | | 15x-199=6x-10 | | 2n+n-6=0 | | 5n+3=23 | | 4.9X=4.4+19.1 | | 50-2x=16x+22 | | 9y^2-6y=3y | | y=-(2/3)5+30 | | 10=-(2/3)x+30 | | 4b+5b+2=0 | | y+2(y-3)=6 | | 5=-(2/3)x+30 | | 58-5x=22+22x | | -1=3+5x-3x | | x+9=5(4x+2) | | -a-a=8 | | -6x^2+8-5+3x+2x-4x^2= |